DISTRIBUSI KETEBALAN GAMBUT DAN SIFAT-SIFAT TANAH DI HUTAN RAWA GAMBUT KALAMPANGAN, KALIMANTAN TENGAH - Indrayanti, Lies; Marsoem, S.N; Prayitno, T.A; Supriyo, H.; Radjagukguk, B (Jurnal Wana Tropika, 2015)
Conducted in peatland forest of Central Kalimantan, Kalampangan, the aim of this research is to study about the distribution of peatland thickness and peatland traits based on peatland thickness differences and the depth of sampling test. Determination of plots are carried out by the path system which is parallel with river. Derived from 12 different points of observation, the result show peatland thickness variations. The range of thickness is between 3,72m – 6,2m. Those peatland thickness is categorized as very deep. Distance from river does not determine the number of thicknesss. Maturity level of the peat is categorized as hemic and sapric. The average volume in 100cm depth is0,15 g.cm-3 and 0,23 g.cm-3 in 50cm depth. Peatland thickness affects moisture content and total Fe. Peatland depth affects moisture content, volume and total Cu. The moisture content and total Cu are lower in 50cm depth compare to 100cm depth. On the other hand, the volume is higher in 50cm depth. Interaction between peatland thickness and sampling test depth affects moisture content and total N content. The highest moisture content is in 4m and 6m thickness and in 100cm depth. Keywords : Deep peat, thickness distribution, physics and chemistry traits